The Influence of Work Discipline and Work Environment on Employee Performance with Work Motivation as an Intervening Variable at PT Jamkrida Riau - Sinaga, Mika Yani Br; Ningsih, Dewita Suryati; Novrianti, Dian Puspita (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This study aims to see the influence of work discipline and work environment on employee performance with work motivation as an Intervening Variable in PT. Jamkrida Riau. This study was conducted using primary data collected from respondents through questionnaires, while respondents consisted of 65 employees of PT. Jamkirda Riau. Then a hypothesis test was carried out using path analysis to see the influence of the independent variable on the dependent variable. The results of this study shows that work discipline has a significant positive effect on employee performance. The work environment has a significant positive effect on employee performance. Work discipline has a significant positive effect on employee motivation. The environment has a significant positive effect on employee motivation. Work motivation has a significant positive effect on employee performance. Work motivation is able to mediate the influence of work discipline on performance. Work motivation is able to mediate the influence of the work environment on performance.